AN UNUSUALLY DIVERSE LLANDOVERY (SILURIAN) DIPLOGRAPTID FAUNA FROM THE SOUTHERN URALS OF RUSSIA AND ITS EVOLUTIONARY SIGNIFICANCE - Koren T.N.; Rickards R.B. (My University, 2004)
This vesiculosus Biozone assemblage of chemically-isolated graptolites from the Orenburg District of Russia was obtained from limestones associated with pillow lavas of the Sakmara Formation of Silurian–Early Devonian age. It comprises 30 species, of which 24 are described. Nine are new, one is a new subspecies, and eight are left under open nomenclature. The assemblage is unique in its diversity of minute biserial graptolites referable to the genera ‘Glyptograptus’, Normalograptus, Sudburigraptus, and Metaclimacograptus; and is unusual in that well-preserved graptolite faunas are rare at this stratigraphical level, which is fixed by the occurrence of Cystograptus vesiculosus (Nicholson) s.l. and Paraclimacograptus innotatus (Nicholson). The following new forms are described: ‘Glyptograptus’tamariscus praecursor subsp. nov., G. mazovoensis sp. nov., G. nikitini sp. nov., G. pavlinovi sp. nov., G. telarius sp. nov., G. zimai sp. nov., Normalograptus legrandi sp. nov., N. melchini sp. nov., N. sobolevskayae sp. nov., and Metaclimacograptus bjerreskovae sp. nov. Five evolutionary lineages are defined within the ‘Glyptograptus’tamariscus (Nicholson) plexus, modifying and extending the pioneer work of Packham (1962). The diverse ‘Glyptograptus’ faunas are considered to be a replacement for the Normalograptus fauna which peaked in the late Ordovician and early Silurian. Metaclimacograptus, although reasonably diverse in its speciation, exhibits a conservative style of evolution with little fundamental change throughout the Llandovery. It is suggested that cortical bandages have species-specific dimensions and micro-features. Some problematical micro- and ultrastructural features are described, notably fibrillar textures, parallel to the fusellar margins, in several species.
Keywords: Silurian; Llandovery; graptolites; diplograptids; Russia; evolution; Paleozoic::Silurian::Llandovery; Палеозой::Силурийская::Лландоверийский